Equisetum thermale sp. nov. (Equisetales) from the Jurassic San Agustín hot spring deposit, Patagonia: Anatomy, paleoecology, and inferred paleoecophysiology - Channing, Alan (2011)
Premise of the study: Dated molecular phylogenies suggest a Cenozoic origin for the crown group of Equisetum. but compression fossil equisetaleans that are morphologically indistinguishable from extant Equisetum and recently discovered anatomically preserved examples strongly suggest an earlier Mesozoic initial diversification. Methods: In situ samples of Equisetum thermale sp. nov. from the Upper Jurassic San Agustín hot spring deposit were collected and studied with the use of polished blocks, thin sections, and light microscopy. Key results: Equisetum thermale exhibits all the morphological and anatomical characteristics of the extant crown group Equisetum. It shows a mixture of features present in the two extant subgenera, e.g., superficial stomata typical of subgenus Equisetum allied with infrequently ramifying stems typical of subgenus Hippochaete. This appears to ally E. thermale with the least derived extant species in the genus Equisetum bogotense (sister species to the two subgenera). Its association of hydromorphic and xeromorphic characters allowed it to grow as an emergent aquatic in physically and chemically stressed geothermally influenced wetlands, where it formed dense monospecific stands. Equisetum thermale, because it is preserved in situ with intact anatomy, provides clear paleoecological, biological, plus inferred paleoecophysiological evidence of adaptations known in extant species. Conclusions: As the earliest unequivocal member of the genus, E. thermale supports the hypothesis of a Mesozoic origin. Its inferred tolerance of a similar range of stresses (e.g., high salinity, alkalinity, and heavy metal concentrations) to that seen in extant Equisetum suggests early evolution and subsequent maintenance of ecophysiological innovations in the genus.